PENERAPAN METODE TALAQQI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA MA MDIA BONTOALA - Muh Anugrah Halim, Mustamin, Ahmad; Abdul Wahab, Muh Aidil Sudarmono R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this classroom action research (CAR) is to examine the application of the talaqqi method in developing the ability to read the Qur'an of class XI students at MA MDIA Bontoala Makassar. This study used a two-cycle CAR design, involving 35 students as participants. Data were collected through observation, interviews, tests, and documentation, then analyzed using percentage and average calculations to measure student activity and their learning outcomes. The application of the talaqqi method for two cycles showed a significant increase in students' ability to read the Qur'an. In the early stages (pre-cycle), the average student score was only 48 (less category), with a success rate of 34.28%. After the first cycle, the average score increased to 70.28 (good category), and the success rate reached 68.57%. In the second cycle, the increase continued with an average score of 84.57 (very good category) and a success rate of 85.71%. These findings confirm the effectiveness of the talaqqi method in improving students' ability to read the Qur'an. Substantial improvement from pre-cycle to cycle II shows the feasibility of this method to be applied in improving the quality of learning the Qur'an. Therefore, this study recommends the integration of the talaqqi method more widely into the Qur'an curriculum at MA MDIA Bontoala Makassar and similar schools. Further research can explore the application of this method at various grade levels and levels of education.